On Installation of Java Programming Learning Assistant System Platform in University Course - Aung, Soe Thandar; Funabiki, Nobuo; Lu, Xiqin; Wai, Khaing Hsu; Jing, Yanhui; Kao, Wen-Chung (IEEE International Conference on Consumer Electronics-China (Online), 2024)
Java has found numerous applications in diverse systems such as servers, smartphones, and embedded systems due to the reliability and portability in object-oriented programming. To facilitate Java programming learning of novice students, we have studied Java Programming Learning Assistant System (JPLAS) and implemented its software platform using Node.js as the web application server. Docker is introduced for easy installations in their own computers of various hardware/software environments by students. In this paper, we explore the errors encountered in the installation and utilization of the JPLAS platform among 56 third-year students enrolled in a Java programming course at Okayama University, Japan, and present their solutions. The result clarified some concerns to be considered at the use of a system developed in a laboratory by the students in a university course with Docker.